2015
DOI: 10.1111/codi.12869
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal surgery and omission of neoadjuvant therapy for upper rectal cancer is associated with a high risk of local recurrence

Abstract: Tumour stage and an involved circumferential resection margin were the most important predictors of local recurrence. For cancer of the upper rectum, partial mesorectal excision was associated with a high risk of local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…This study has shown a significant reduction in the risk of local recurrence after a local MDT‐directed quality assurance programme in patients with cancer of the upper rectum. A previous report on local recurrence in patients who had PME for upper rectal cancer was disappointing, and suboptimal surgery and/or selection was evident.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This study has shown a significant reduction in the risk of local recurrence after a local MDT‐directed quality assurance programme in patients with cancer of the upper rectum. A previous report on local recurrence in patients who had PME for upper rectal cancer was disappointing, and suboptimal surgery and/or selection was evident.…”
Section: Discussionmentioning
confidence: 94%
“…A concerningly high rate of local recurrence (13⋅5 per cent) in patients with upper rectal cancer after PME has been reported previously 11 . Evidence of suboptimal surgery and/or selection was clear 9,11 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Historically, RC has been associated with high risk of local recurrences, and poor long-term survival prognosis. The last decades' improvements in treatment have led to a marked decrease in the risk of local recurrence and mortality from RC [3,4]. The risk of local recurrence is 7-9%, and the overall five-year survival rate is now 62% [2,3].…”
mentioning
confidence: 99%
“…The last decades' improvements in treatment have led to a marked decrease in the risk of local recurrence and mortality from RC [3,4]. The risk of local recurrence is 7-9%, and the overall five-year survival rate is now 62% [2,3]. About 65-70% of RC patients receive treatment with a curative intent.…”
mentioning
confidence: 99%